The Influence of Borrower Characteristics, Loan Size, Business Income and Business Experience on Cooperative Loan Returns: Pengaruh Karakteristik Peminjam, Besar Pinjaman, Pendapatan Usaha dan Pengalaman Usaha Terhadap Pengembalian Pinjaman Koperasi - Oktavia Fajriyati; Sriyono Sriyono (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of Borrower Characteristics, Loan Amount, Business Income and Business Experience on Cooperative Loan Repayment in Savings and Loan Cooperatives and Multipurpose Cooperatives in Candi District, Sidoarjo Regency. This research is a type of quantitative research. The sample used in this study was 150 respondents at the Savings and Loans Cooperative and Multi-Business Cooperative in Candi District, Sidoarjo Regency. The sampling technique used in this research is purposive sampling. Data was collected by distributing questionnaires. The research method to test the quality of the data using validity and reliability tests. Meanwhile, for data analysis using SEM (Structural Equation Modeling) with AMOS 24 software. The results of this study indicate that borrower characteristics, loan size, business income and business experience have a positive and significant impact on cooperative loan repayments.